Corn Silage Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Ibendahl, Gregg (My University, 2015)
This publication contains information for a projected budged reflecting expected income and cost based on typical corn silage production practices in the northeast region of Kansas.
MF2364_2015_04
Keywords: MF2364; Economics; Crops; MF